The Effectiveness of the Pre-approval System in Protecting Public Transactions against the Risks of Corruption - Naidji, Said (Journal of Legal Studies and Researches, 2026)
Public contracts are subject to several types of oversight during their formation and execution stages. The most prominent is ex-ante oversight, which is divided into internal and external oversight. Internal oversight is conducted by the contracting authority through the opening of bids and their evaluation, which involves examining, analyzing, and monitoring the implementation of offers. External oversight is entrusted to public procurement committees, which are established within each contracting authority. Their purpose is to ensure that public contracts comply with the applicable legislation and regulations.